Answer:
3x = 3 + 2y -------------> 3x - 2y = 3 {subtracted 2y from each side of top equation}
(-4/3)x + y = -2/3 ------> -4x + 3y = -2 {multiplied bottom equation by 3}
3x - 2y = 3 ------> 12x - 8y = 12 {multiplied top equation by 4}
-4x + 3y = -2-----> -12x + 9y = -6 {multiplied bottom equation by 3}
12x - 8y = 12
-12x + 9y = -6
--------------
y = 6 {added the two equations}
3x = 3 + 2y {original top equation}
3x = 3 + 2(6) {substituted 6, in for y, into top equation}
3x = 3 + 12 {multiplied}
3x = 15 {added}
x = 5 {divided each side by 3}
x = 5 and y = 6
Explanation: